Novel heterometallic uranyl-transition metal materials: Structure, topology, and solid state photoluminescence properties - Gomez, Germán Ernesto (2019)
Six new uranyl hybrid materials have been synthesized solvothermally utilizing the ligands 2,2′-bipyridine-3,3′-dicarboxylic acid (H2L) and 2,2′:6′,2′′-terpyridine (TPY). The six compounds are classified as either molecular complexes (I0O0 connectivity), [(UO2)(L)(TPY)]·H2O (1), [Ni(TPY)2][(UO2)(L)2]·3H2O (2), and [Cu(TPY)2][(UO2)(L)2]·3H2O (3), or 3D metal–organic frameworks (MOFs, I0O3 connectivity), [Cu2(UO2)2(OH)(C2H3O2)(L)3(TPY)2]·6H2O (4), [Zn2(UO2)2(OH)(NO3)(C2H3O2)(L)3(TPY)2]·4H2O (5), and Na[Ni(UO2)3(OH)(O)(L)3]·9H2O (6). A discussion of the influence of transition metal incorporation, chelating effects of the ligand, and synthesis conditions on the formation of uranyl materials is presented. The structure of compound 6 is of particular note due to large channel-like voids with a diameter of approximately 19.6 Å. A topological analysis of 6 reveals a new topology with a 9-nodal 3,3,3,3,3,3,3,4,5-connected network, designated geg1 hereafter. Further, solid state photoluminescence experiments show emission and lifetimes values consistent with related uranyl compounds.